Worldwide survey on implantation of and outcomes for conduction system pacing with His bundle and left bundle branch area pacing leads - Perino, Alexander C.; Wang, Paul J.; Lloyd, Michael; Zanon, Francesco; Fujiu, Katsuhito; Osman, Faizel; Briongos-Figuero, Sem; Sato, Toshiaki; Aksu, Tolga; Jastrzebski, Marek; Sideris, Skevos; Rao, Praveen; et al. (Journal of interventional cardiac electrophysiology, 2023)
BACKGROUND: Adoption and outcomes for conduction system pacing (CSP), which includes His bundle pacing (HBP) or left bundle branch area pacing (LBBAP), in real-world settings are incompletely understood. We sought to describe real-world adoption of CSP lead implantation and subsequent outcomes. - METHODS: We performed an online cross-sectional survey on the implantation and outcomes associated with CSP, between November 15, 2020, and February 15, 2021. We described survey responses and reported HBP and LBBAP outcomes for bradycardia pacing and cardiac resynchronization CRT indications, separately. - RESULTS: The analysis cohort included 140 institutions, located on 5 continents, who contributed data to the worldwide survey on CSP. Of these, 127 institutions (90.7%) reported experience implanting CSP leads. CSP and overall device implantation volumes were reported by 84 institutions. In 2019, the median proportion of device implants with CSP, HBP, and/or LBBAP leads attempted were 4.4% (interquartile range [IQR], 1.9-12.5%; range, 0.4-100%), 3.3% (IQR, 1.3-7.1%; range, 0.2-87.0%), and 2.5% (IQR, 0.5-24.0%; range, 0.1-55.6%), respectively. For bradycardia pacing indications, HBP leads, as compared to LBBAP leads, had higher reported implant threshold (median [IQR]: 1.5 V [1.3-2.0 V] vs 0.8 V [0.6-1.0 V], p = 0.0008) and lower ventricular sensing (median [IQR]: 4.0 mV [3.0-5.0 mV] vs. 10.0 mV [7.0-12.0 mV], p < 0.0001). - CONCLUSION: In conclusion, CSP lead implantation has been broadly adopted but has yet to become the default approach at most surveyed institutions. As the indications and data for CSP continue to evolve, strategies to educate and promote CSP lead implantation at institutions without CSP lead implantation experience would be necessary.
Gesehen am 07.11.2024